2012
DOI: 10.1016/j.jpor.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal expansion mismatch on the Y-TZP/veneer interfacial adhesion determined by strain energy release rate

Abstract: Thermal residual stresses and strain energy release rates were correlated. Slight compressive stresses in the region of -20MPa were beneficial for the Y-TZP/veneer interfacial adhesion. Stresses higher or lower than this value exhibited decreased adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…24,25 Algunos autores sugieren que una tensión residual excesiva en la cerámica de recubrimiento sometida a cargas oclusales podría ser uno de los factores que propician la aparición de chipping o delaminación de la cerámica de recubrimiento con estructuras a base de zirconia. 7,21,26 Se ha descrito una relación entre la utilización de protocolos de enfriamiento lento y disminución de la fuerza adhesiva de la cerámica de recubrimiento a la zirconia, 20 este hallazgo probablemente sea una explicación a los resultados obtenidos en esta investigación, donde la resistencia adhesiva máxima es de 16,36 MPa. Estos resultados son menores al compararlos con resultados de estudios que se realizaron sin la utilización de protocolos de enfriamiento lento y promediaron resistencia adhesiva de 20 hasta 35 Mpa.…”
Section: Discussionunclassified
“…24,25 Algunos autores sugieren que una tensión residual excesiva en la cerámica de recubrimiento sometida a cargas oclusales podría ser uno de los factores que propician la aparición de chipping o delaminación de la cerámica de recubrimiento con estructuras a base de zirconia. 7,21,26 Se ha descrito una relación entre la utilización de protocolos de enfriamiento lento y disminución de la fuerza adhesiva de la cerámica de recubrimiento a la zirconia, 20 este hallazgo probablemente sea una explicación a los resultados obtenidos en esta investigación, donde la resistencia adhesiva máxima es de 16,36 MPa. Estos resultados son menores al compararlos con resultados de estudios que se realizaron sin la utilización de protocolos de enfriamiento lento y promediaron resistencia adhesiva de 20 hasta 35 Mpa.…”
Section: Discussionunclassified
“…This may be important, as stress distribution at a bilayer interface is significantly affected by the layer thickness of the components 13,29) . Recently, strain energy release rate has been evaluated with zirconia core and veneer ceramics and has been found to be a reliable method for analysing interfacial adhesion 14,15) . These studies revealed that interfacial adhesion between the materials is significantly influenced by residual stresses, which are themselves affected by the thermal characteristics of the components.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that interfacial adhesion between the materials is significantly influenced by residual stresses, which are themselves affected by the thermal characteristics of the components. In this context, slight compressive stresses of about −20 MPa (correlating to a CTE mismatch of ≈1.4 ppm K −1 ) in the adhesion zone have been reported to be beneficial for zirconia/veneer interfacial adhesion 14) . Beside the thermal characteristics of these materials, these stresses could also be influenced by modulating the cooling rate within the firing process 15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations